2020
DOI: 10.1007/s00068-020-01321-4
|View full text |Cite
|
Sign up to set email alerts
|

A meta-analysis on anticoagulation after vascular trauma

Abstract: Purpose There is much debate regarding the use of anticoagulation following vascular trauma. The aim of this meta-analysis was to compare the outcome of trauma following administration of anticoagulation medication. Methods The literature search was carried out using Ovid MEDLINE and PubMed databases to search for keywords and MeSH terms including "Anticoagulation", "Vascular Surgery", "Vascular Trauma", "Vascular Repair", "Repair" and "Wounds and Injuries". Results Use of anticoagulation was associated with a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 44 publications
0
6
0
Order By: Relevance
“…The UT Houston Score may be a reasonable way to protocolize risk-stratified vascular surgery consultation. Although contraindications to systemic anticoagulation are frequent in trauma, some studies report a benefit to intraoperative and postoperative anticoagulation for arterial injuries, suggesting that systemic anticoagulation and early antiplatelet therapy may be beneficial in high-risk patients 25–28 . In the current study, postoperative medications were provider dependent and differed between trauma and vascular surgeons.…”
Section: Discussionmentioning
confidence: 74%
See 1 more Smart Citation
“…The UT Houston Score may be a reasonable way to protocolize risk-stratified vascular surgery consultation. Although contraindications to systemic anticoagulation are frequent in trauma, some studies report a benefit to intraoperative and postoperative anticoagulation for arterial injuries, suggesting that systemic anticoagulation and early antiplatelet therapy may be beneficial in high-risk patients 25–28 . In the current study, postoperative medications were provider dependent and differed between trauma and vascular surgeons.…”
Section: Discussionmentioning
confidence: 74%
“…Although contraindications to systemic anticoagulation are frequent in trauma, some studies report a benefit to intraoperative and postoperative anticoagulation for arterial injuries, suggesting that systemic anticoagulation and early antiplatelet therapy may be beneficial in high-risk patients. [25][26][27][28] In the current study, postoperative medications were provider dependent and differed between trauma and vascular surgeons. Future protocolized administration of a combination of antiplatelet and anticoagulant medications may be beneficial for high-risk patients in the absence of contraindications.…”
Section: Discussionmentioning
confidence: 94%
“…to the popliteal artery), but are single institutional and/or review retrospective data. A recent metanalysis that included eight such studies from 1988-2017 1,3,[20][21][22][23][24][25] examined a composite outcome for use of anticoagulants following arterial repair. This study included all anatomic locations of trauma, but did not focus on those with repair with a vein, nor did it consider postoperative AP therapy.…”
Section: Discussionmentioning
confidence: 99%
“…The optimal use of postoperative antithrombotic (AT) therapy in trauma patients presenting with arterial injury is not well-established, specifically in patients requiring reconstruction with an autologous vein graft. [1][2][3][4] While there is concern for postoperative hemorrhage in the setting of traumatic injury (at the site of vascular injury or at alternative site(s) of injury], there is also a risk of thrombosis of the vascular reconstruction. In the elective setting, patients undergoing vascular reconstruction with a vein graft are routinely treated with AT therapy; however, there is no consensus to utilize AT therapy in the trauma patient.…”
Section: Introductionmentioning
confidence: 99%
“…The treatment of this type of fracture is challenging. A meta-analysis demonstrated that the use of systemic anticoagulants in the context of vascular trauma is significantly associated with a reduction in the rates of arterial patency failure and amputation, as well as a reduced risk of VTE development [6]. Therefore, we also used heparin after vascular anastomosis in Gustilo-Anderson type IIIC open fractures; however, the patient developed HIT, which led to lower-extremity ischemia.…”
Section: Introductionmentioning
confidence: 99%